Online Education During Pandemic Times: Advantages and Disadvantages - Moise, Daniel; Diaconu, Amelia; Oancea Negescu, Mihaela Diana; Gombos, Carol Cristina (European Journal of Sustainable Development, 2021)
The latest Pandemic has changed not only our lifestyle behavior, but at the same the manner how we work, study, and evolve. We witnessed work from home, or remote working, as well as learning from home changes. The shift from the physical classroom to the online classroom came with advantages, but also with some, disadvantages. In this article, we conducted a research to discover undergraduate and graduate students’ perceptions towards online education. Students and professors are detached for the time being from their universities into online education platforms and video conference rooms, but not without other difficulties and challenges for the academic community. Some universities already had some practice and knew how to manage and use online platforms for different cycle types like: part-time or distance learning programs. Other universities appealed to platforms offered by international organizations like Microsoft or Google. The novelty was that not only the courses and seminars are held online and exams as well, proving to be a provocative issue, both for students and professors. We discovered different factors that influence online education and learning satisfaction. One of the main discoveries was that the future seems to be towards a blended learning system combining physical and online teaching.